Implementation of Structuring and Empowering Street Vendors on Ahmad Yani, Sukabumi City - Nasywa Dini; Muhammad Rijal Amirulloh; Andi Mulyadi (Universitas Muhammadiyah Gorontalo, 2026)
The increasing number of street vendors (PKL) on Jalan Ahmad Yani, Sukabumi City, has caused problems in the use of sidewalks and public spaces, which has an impact on traffic congestion and declining order in urban areas. This study aims to analyze the implementation of policies for structuring and empowering Street Vendors based on the theory of policy implementation sing a policy implementation theory framework that encompasses four dimensions: communication, resources, disposition, and bureaucratic structure. This study uses a qualitative method with a descriptive approach. The data collection technique was carried out through observation, interviews, and documentation involving the Sukabumi City Cooperatives, Micro Enterprises, Industry and Trade Office, the Sukabumi City Pamong Praja Police Unit, and street vendors on Jalan Ahmad Yani. Data analysis uses the Miles and Huberman model, which includes data reduction, data presentation, and conclusions drawn. The results of the study show that the implementation of the policy has been carried out through socialization, coaching, supervision, and control activities. However, the implementation has not been running optimally because there are still limited resources, low street vendor compliance, inadequate relocation locations, and inconsistent supervision. This study concludes that the implementation of street vendor structuring policies requires strengthening inter-agency coordination, continuous supervision, and the provision of strategic relocation locations to create a balance between urban order and community economic sustainability.